Metallothionein Protein Modeling from Pseudomonas aeruginosa PAO1 as A Metal Biosorber Candidate - Fajri Ikhsan; Ahmad Shulhany; Syarif Abdullah (Jurnal Biodjati, 2023)
Metallothionein is a protein that is well known to play a role in metal metabolism in bacterial cells. Metallothionein is a multifunctional protein that has the potential to be used as a metal adsorbing agent. Pseudomonas aeruginosa is a ubiquitous gram-negative and rapid-growth bacterium. In addition, the complete genome of Pseudomonas aeruginosa has been largely known. Pseudomonas aeruginosa PAO1 is a strain of Pseudomonas aeruginosa that the complete genome of this strain is easily accessible in NCBI. These features make Pseudomonas aeruginosa PAO1 become a common model in bacterial studies. This research aimed to find and model the putative metallothionein of Pseudomonas aeruginosa PAO1. This research was carried out by bioinformatic and protein homology methods. Based on the results, the putative metallothionein of Pseudomonas aeruginosa PAO1 was found in the bacterial genome at base sequence of 2355918 to 2356157. The putative metallothionein-encoding gene of Pseudomonas aeruginosa PAO1 has a size of 240 bp. The translation result of the gene showed that the putative metallothionein of Pseudomonas aeruginosa PAO1 has 79 amino acids. The modeling result showed the 3D structure of the putative metallothionein of Pseudomonas aeruginosa PAO1 is similar to the metallothionein 3D structure of Pseudomonas fluorescens Q2-87. The 3D structure of the putative metallothionein of Pseudomonas aeruginosa PAO1 was dominated by turn and coil, but contained 1 α-helix structure and 2 β-sheet structures. Based on protein analysis, it was found that the putative metallothionein of Pseudomonas aeruginosa PAO1 has 1 metal-binding cluster with 10 amino acids and the most important amino acid residue is Cysteine . Even though, there was 1 Histidine amino acid residue on the metal-binding cluster.